Functional Analysis of MsepOR13 in the Oriental Armyworm Mythimna separata (Walker) - Zhang, Kunpeng; Feng, Yilu; Du, Lixiao; Gao, Shanshan; Yan, Hang; Li, Kun; Liu, Nana; Wu, Junxiang; Wang, Guirong (Frontiers in Physiology, 2019)
Olfaction in insects has a critical role in recognizing the host, finding food, and choosing mating partners, as well as avoiding predators. Olfactory receptors (OR), which are housed in the dendritic membrane of sensory neurons and extended into the lymph of sensilla on insect antennae, are responsible for the detection of volatile compounds in insects. In the present study, we identified an OR gene, named MsepOR13, in the oriental armyworm Mythimna separata (Walker). Quantitative real-time polymerase chain reaction revealed that MsepOR13 was expressed mainly in the antennae of male and female moths. In in vitro heterologous expression experiments, MsepOR13 was widely tuned to 32 of the 67 different compounds tested. Furthermore, MsepOR13 responded to eugenol at a low concentration of 10−9 M, with an EC50 value of 3.91×10−6 M. The high sensitivity suggests an important role for the OR13 gene in the moth olfactory system.